Місце і роль сім’ї та родини у вихованні дітей: етнонародознавчий аспект - Михайлишин, Романа (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article emphasizes that the upbringing is a systematic and purposeful influence on a child, her/his mind, soul and body, which depends not only on the social and political structure of society, its internal and external needs, state building processes, but also on the national traits, outlook and culture of the nation. The author states that learning the experience how to revive and preserve the folk traditions of the family education makes it possible to foster the modern young generation as socially active, nationally conscious citizens, and worthy successors of their folk material and sacred values. The main focus is laid on a family as the initial center of the nation, society, state, and on parents as the main native educators of a child
Keywords: family; relatives; education of a child; family education